Prevalence of Some Common Human Traits: An Updated Survey Report From Rajshahi University Campus, Bangladesh (Bangladesh Journal of Zoology, 2021)
Prevalence of some common human traits viz., body weight, height and body mass index (BMI), pattern baldness, body hair, chin, colour blindness, cheek dimples, earlobes, length of index finger, lips, nose, polydactyly, tongue and widow’s peak, and ABO blood groups along with their Rh-D antigen, were recorded and analyzed from 500 male and 1000 female students of the Rajshahi University (RU) Campus. Results showed that body weights of the male students (66.42±8.92 kg) were significantly higher (t= 35.14; P A (22.4) > AB (15.8) and O (34.8) > B (34.4) > A (21.9) > AB (8.9), respectively. As a whole, 85.4% males and 98.0% females were Rh-positive where the blood group phenotypes did not affect body weight, height and BMI of the subjects (r=0.012; P=0.63). The relevance of these findings to the physical, physiological, social and clinical well-being of the humans has been discussed.Bangladesh J. Zool. 49 (2): 215-228, 2021